Understanding the effect of tailored heat treatment on Zr-modified Al7075 fabricated by laser powder bed fusion - Nicolas Nothomb; Ignacio Rodriguez-Barber; Marie-Noëlle Avettand-Fénoël; María Teresa Pérez Prado; Maya Marinova; Aude Simar (Materials & Design)
Despite high-strength aluminium alloys now being widely processed by laser powder bed fusion (L-PBF), a specifically designed heat treatment (HT) for L-PBF Al7075 has yet to be identified and the microstructural features responsible for strengthening remain to be fully understood. In this study, fully dense Al7075+1.8%Zr was processed without hot cracking. High temperature heat treatments between 350°C and 525°C were adopted, attaining the highest hardness (162HV) at 425°C followed by an artificial ageing (AA). This heat treatment produced a yield strength of 515 MPa and an elongation at fracture of 12%. To understand the effect of this tailored low-temperature HT, comparisons were made with a classical T6 HT (1 h at 470°C followed by AA). Transmission electron microscopy analyses revealed a higher volume fraction of Al3Zr L12 secondary precipitates with the 425°C HT than with the 470°C HT. These hardening precipitates were quantified as the main contributor to strengthening, accounting for 207 MPa. The 425°C HT prevented the over-ageing Zr precipitates generated by the 470°C HT, while inhibiting recrystallization. η′ precipitates played a minor role in the tensile properties as they were nearly absent from the microstructure due to the excessive evaporation of Mg and Zn during L-PBF.